Native consortia of arbuscular mycorrhizal fungi and Trichoderma control Meloidogyne incognita in habanero pepper - Cristobal-Alejo, Jairo; Ramos Zapata, José Alberto; Garruña Hernández, Rene; Reyes Estébanez, María Manuela; Herrera-Parra, Elizabeth (Ecosistemas y Recursos Agropecuarios, 2023)
Root-knot nematodes affect the production of habanero pepper (Capsicum chinense Jacq.) and the use of antagonistic microor- ganisms is an option for their control. The objective was to evaluate native consortia of arbuscular mycorrhizal fungi (AMF) and Trichoderma spp. (TRI) for the management of M. incognita (Mi) in C. chinense. Five treatments established under protected conditions: AMF + Mi, TRI + Mi, AMF + TRI + Mi, Vydate 24% nematicide (Oxamil) + Mi and a control with only Mi. Each treatment had 15 replicates. The AMF + Mi treatment decreased the galling index, the number of eggs and females by 56, 48 and 26.29% in relation to Oxamil. The highest growth of the plants achieved with AMF + Mi with higher effects than the nematicide and control. The AMF + Mi and AMF + TRI + Mi treatments promoted better physiological functioning of the plants.